Planar Chiral Ferrocene Lithium Amide Bases: A New Generation of Bases for Asymmetric Synthesis - Arnall-Culliford, Jennifer (2002)
The design and preparation of a new class of planar chiral ferrocenyl lithium amide bases is described. Work commenced on preparing N./V-dimethyl-l-ferrocenylethylamine derivatives. Electrophilic amination was attempted with a variety of reagents, but no diamines were ever obtained. The introduction of a boronic acid group was also attempted, but no products were isolated. Finally, nitration followed by reduction was investigated, but again proved unsuccessful, resulting only in the preparation of a dimer of the starting amine, 2,2'-bis-[ 1 -(//, A-dimethylamino)-ethyl]-l, l'-biferrocenyl. Our attention turned to derivatives of MN-diisopropylferrocene carboxamide. Metallation, followed by quenching with iodine gave Af,N-diisopropyl-2- iodoferrocene carboxamide. Copper(I) oxide mediated coupling of the iodide with either acetic acid or phthalimide gave access to ortho-oxygen and nitrogen donor groups. A new class of planar chiral bases (N-alkyl-(2- alkoxyferrocenyl)methylamines) were prepared from this starting material by reduction of the amide, followed by substitution of the diisopropylamine with a range of primary amines. Assays were carried out using the deprotonation of 4-tert-butylcyclohexanone and trapping of resultant enolate with TMSC1. Bases having a plane of chirality as the only stereochemical element, disappointingly, gave nearly racemic silyl enol ether, however low optical purities were recorded for bases consisting of both central and planar chirality. A non-chelating planar chiral lithium amide base was prepared (^S}-A^-rer/-butyl-(2-methylfen'ocenyl)-t methylamine, however this too gave nearly racemic silyl enol ether in the assay reaction. The synthesis of planar chiral azaferrocenyl bases was attempted by sequential complexation of lithiated pyrrole-2-methanol and lithium pentamethyl- cyclopentadienide with iron(II) chloride, followed by acylation of the pendant alcohol. However, all attempts to substitute the acetate with an amine proved unsuccessful.